Nude Photography, Eksploitasi Tubuh Pengatasnamaan Seni - KHEYENE MOLEKANDELLA BOER (Universitas Muhammadiyah Yogyakarta, 2012)
Photography as media of communication has become more and more popular today. The existence of photography has now entered sensual domain which is done in the name of art. This type of photography is known as “nude photography”. Nude photography is a photography technique which is full of lighting trick to show up the artistic side of human bodies, especially women. This kind of art has become commodity and changed into a masterpiece which has high value. Then women are forced to follow the beauty standard which is defined by men to avoid discrimination by the society. . This paper tries to correlate the relationship between body exploitation and art by referring to the concept of feminism which proves that there are inequities between men and women. Nude photography has violated ethics by showing off the vulgarity of each woamn body part. Women’s bodies, in fact, always become an endless discussion. This kind of exploitation cannot be minimized if there are many misuses in the name of art in patriarchal culture. The question is what women should do in order to save themselves from exploitation. Keywords: Nude photography, Exploitation of woman’s body, Art